Evaluation of Granada Agar Plate for Detection of Streptococcus agalactiae in Urine Specimens from Pregnant Women - Tamayo, Javier (American Society for Microbiology, 2004)
The Granada agar plate (GAP; Biomedics SL, Madrid, Spain) was evaluated for the detection of group B streptococci (GBS) in urine specimens from pregnant women submitted for testing for asymptomatic bacteriuria and was compared with blood agar (BA [Columbia agar with 5% sheep blood]; bioMérieux, Marcy l'Etoile, France). The GAP detected 103 out of 105 GBS, whereas BA detected only 50. Use of the GAP could be a good method for the detection of GBS in urine specimens from pregnant women.